2020
DOI: 10.1111/arcm.12538
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of palace lantern tassels preserved in The Palace Museum, Beijing, by UPLC‐ESI‐Q‐TOF

Abstract: Palace lanterns were important and highly visible decorations in the imperial palace in Beijing, China, during the Qing dynasty (1636-1912. Most lanterns had colourful tassels made of fibres. The study performed a comprehensive investigation of the materials and dyes used for palace lantern tassels preserved in The Palace Museum, Beijing. Eight samples with different colours, including yellow, green and red, from five palace lanterns were analysed. By using ultra-performance liquid chromatography combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, at the time of this writing, available literature on the quality of textiles based on fringes or tassels is limited. The findings of one study [32] indicated that dyes and materials could impact the quality of tassels of a textile. For example, a combination of ultra-performance liquid chromatography and time-of-flight spectrometry revealed that tassels (all made from silk fabric) that were directly dyed (no mordant added) with cork tree were more resistant to fading or bleeding due to light as compared to similar, yellow-colored tassels that were directly dyed with cheaper-cost turmeric and had a lesser degree of lightfastness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the time of this writing, available literature on the quality of textiles based on fringes or tassels is limited. The findings of one study [32] indicated that dyes and materials could impact the quality of tassels of a textile. For example, a combination of ultra-performance liquid chromatography and time-of-flight spectrometry revealed that tassels (all made from silk fabric) that were directly dyed (no mordant added) with cork tree were more resistant to fading or bleeding due to light as compared to similar, yellow-colored tassels that were directly dyed with cheaper-cost turmeric and had a lesser degree of lightfastness.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on instrumental approaches to determine textile quality is abundant [26][27][28][29][30][31][32]. There also is consumer-based research on people's perceptions of the quality of textiles, but this type of research is quite limited [33].…”
Section: Introductionmentioning
confidence: 99%